Walking football for older adults: Systematic review - José M. Gamonales; Elías Martín-Casañas; Víctor Hernández-Beltrán; Luisa Gámez-Calvo; Kiko Leon; Jesús Muñoz-Jiménez (Federación Extremeña de Balonmano; University of Extremadura, 2021)
The study aims to conduct a systematic review based on the results found around the Walking football, in order to know the sport rules and the benefits of it practice for health and general well-being in older adults. The search phrases were always introduced in English and computerized databases: Web of Science, PubMed, Science Direct and Google Academy. Two search phrases were used: "Walking football - And - Older adults" and "Walking soccer - And - Older adults". To limit the search, a series of inclusion and exclusion criteria were established in order to select the most appropriate documents on the subject. After the review, 18 manuscripts published up to November 2020, which met the inclusion criteria, were selected. The selected documents show that the Walking Football has benefits on a social, psychological, and physiological level. In addition, the Walking Football regulations are adapted to each training group, in order to minimize the risk of injury in older adults during its practice. Finally, the documents related to the subject are mainly Journal articles, published in 2019, and are found in the Google Academic database.